A Convenient Route to Monoalkyl‐Substituted Phosphanylboranes (HRP–BH2–NMe3): Prospective Precursors to Poly[(alkylphosphino)boranes]. Issue 17 (24th April 2016) - Stauber, Andreas; Jurca, Titel; Marquardt, Christian; Fleischmann, Martin; Seidl, Michael; Whittell, George R.; Manners, Ian; Scheer, Manfred
Abstract : A simple method to access borylphosphonium iodides [RH2 P–BH2 · NMe3 ]I (1a : R = Me;1b : R = Et;1c : R = n Pr) by the addition of iodoalkanes to PH2 –BH2 · NMe3 was developed. Complexes1a –c were characterized by multinuclear NMR spectroscopy, and1a and1b additionally by single‐crystal X‐ray diffraction. It was possible to synthesize the Lewis‐base‐stabilized organosubstituted phosphanylborane MePH–BH2 · NMe3 (2 ) from [MePH2 –BH2 · NMe3 ]I (1a ). Thermolysis of2 generated a soluble, low‐molecular‐mass poly(alkylphosphinoborane) consisting of at least 40 repeat units, as identified by ESI‐MS. These results are promising for the future preparation of a wide range of Lewis‐base‐stabilized phosphanylboranes, which are of interest as precursors to poly[(alkylphosphino)boranes] and are otherwise difficult to access by conventional metal‐catalyzed methods. Abstract : A route for the synthesis of monoalkyl‐substituted Lewis‐base‐stabilized phosphinoboranes via borylphosphonium precursors is presented. Mild thermolysis of the Lewis‐base‐stabilized methylphosphinoborane generates the corresponding polymer consisting of at least 40 repeat units, which exemplifies the applicability of this method.